2022
DOI: 10.3389/fpls.2022.885984
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Plant and Microbe Nutrient Limitation Patterns During Natural Vegetation Restoration

Abstract: Vegetation restoration is assumed to enhance carbon (C) sequestration in terrestrial ecosystems, where plant producers and microbial decomposers play key roles in soil C cycling. However, it is not clear how the nutrient limitation patterns of plants and soil microbes might change during vegetation restoration. We investigated the nutrient limitations of the plant and microbial communities along a natural vegetation restoration chronosequence (1, 8, 16, 31, and 50 years) following farmland abandonment in Qinli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Our study found that the influence of land-use change was more predominant at the upslope than at the check dam since the erosion processes accelerated nutrient loss. Previous studies have reported a subsequent P limitation of plants after the microbial P limitation (Cui et al 2022;Xue et al 2022), therefore, the P deficiency issue of the revegetated forest on hillslopes should be considered for the local government. It is especially important since the increasing vegetation biomass and water deficiency (Jia et al 2019) would aggravate microbial P limitation with the development of the revegetated forest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found that the influence of land-use change was more predominant at the upslope than at the check dam since the erosion processes accelerated nutrient loss. Previous studies have reported a subsequent P limitation of plants after the microbial P limitation (Cui et al 2022;Xue et al 2022), therefore, the P deficiency issue of the revegetated forest on hillslopes should be considered for the local government. It is especially important since the increasing vegetation biomass and water deficiency (Jia et al 2019) would aggravate microbial P limitation with the development of the revegetated forest.…”
Section: Discussionmentioning
confidence: 99%
“…At global scales, microbial metabolism in high-latitude grasslands and low-latitude forests was predominantly limited by soil nitrogen (N) and phosphorus (P), while these limitations were alleviated in agriculture ecosystems due to fertilization (Camenzind et al 2018;Cui et al 2021;Turner et al 2018). Previous site-level studies have investigated microbial metabolic limitations focusing on land-use type (Mganga et al 2016), plant species (Wobeng et al 2020), rhizosphere (Cui et al 2019), natural succession stage (Xue et al 2022), vegetation restoration period after anthropogenic forest clearcut (Kang et al 2022) or farmland abandonment (Deng et al 2019). For example, Deng et al (2019) reported a downward unimodal trend of microbial C limitation and a reversed pattern of microbial P limitation during the 30 years of vegetation restoration in an abandoned agroecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms of these interactions and the processes driving changes in soil microbes are still unknown, especially in the case of polluted soil and interactions with nanomaterials or nanoparticles. Research to date has focused on the role of soil microbes as relates to plant mineral nutrition [130], improving the efficiency of fertilizers [131], remediation of degraded mine soils [131], soil microbial communities affecting plant productivity under climate change [132], plants and microbes for restoring soil fertility [133], and plants and microbes for restoration of natural vegetation [134]. Restoring soil fertility utilizing the soil-plant-microbes nexus depends on the biological activity of plants, root exudates, and soil microbial activities and their enzymes, as well as the presence of pollutants or agrochemicals.…”
Section: Soil-plant-water-microbe Interactionsmentioning
confidence: 99%
“…Soil extracellular enzymes are essential facilitators of decomposition [6]. Soil microorganisms typically generate a range of enzymes to enhance the decomposition of organic matter and acquire resources that are bound within it, particularly in situations where they encounter limitations in energy and/or nutrients [1,[11][12][13]. Therefore, organic matter's decomposition potential and quality could be reflected by the variety and activities of extracellular enzymes and the activities and metabolism of microorganisms in the soil [14,15].…”
Section: Introductionmentioning
confidence: 99%